How Good Corporate Governance, Firm Size, and Dividend Policy Affect Firm Value? Evidence on 100 Non-Financial Companies in Asia - Nilam Cahya; Gatot Nazir Ahmad; Sholatia Dalimunthe (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine the effect of Good Corporate Governance (GCG), firm size, and dividend policy on firm value in 100 non-financial companies in Asia that are included in the Forbes version of The World's Biggest Public Company in 2017-2020. The independent variables used in this study are Good Corporate Governance (GCG) (number of the board of directors and audit committee), Firm Size (total assets), and dividend policy (Dividend Payout Ratio). The dependent variable used in this study is firm value (Tobins'Q). The source of data used in this study is secondary data sourced from annual reports and company financial statements for the 2017-2020 period. The sampling method used purposive sampling technique. The model used in this study is the Random Effect Model (REM). The results obtained are that the variables of the board of directors, audit committee, and firm size have no effect on firm value, while the dividend policy variable has a positive effect on firm value. This results are in line with agency theory which requires company managers to think of the best solution to increase shareholder wealth